Methodological challenges in the analysis of agrifood systems: a mixed-method approach - Mario Fernández-Zarza; Carmen Lozano-Cabedo; Santiago Amaya-Corchuelo; Encarnación Aguilar Criado (Entreciencias: Diálogos en la Sociedad del Conocimiento)
Objective: The main goal of this paper consists in analyzing the potential of mixed methods used in the study of two agrifood systems: Iberian ham (Spain) and chorizo from the Toluca Valley (Mexico).